Supplementary Figures S1-S4 from Neoadjuvant Pembrolizumab and Radical Cystectomy in Patients with Muscle-Invasive Urothelial Bladder Cancer: 3-Year Median Follow-Up Update of PURE-01 Trial - Giuseppe Basile (15051269) (2025)
Supplementary Figure 1: Study flow-chart. Supplementary Figure 2: Kaplan-Meier curves of event-free survival according to tertile-split tumor mutational burden. Supplementary Figure 3. Kaplan-Meier curves of recurrence-free survival according to the molecular subtype. Supplementary Figure 4: PD-L1 staining values (CPS percentages) according to molecular subtypes, split by the three subtyping classifiers GSC/Decipher, Consensus classification, and TCGA.